2005
DOI: 10.2337/diacare.28.8.1890
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Quality Improvement Intervention to Improve Diabetes Care in Primary Care Settings

Abstract: OBJECTIVE -To assess the impact of a quality improvement (QI) intervention on the quality of diabetes care at primary care clinics.RESEARCH DESIGN AND METHODS -Twelve primary care medical practices were matched by size and location and randomized to intervention or control conditions. Intervention clinic staff were trained in a seven-step QI change process to improve diabetes care. Surveys and medical record reviews of 754 patients, surveys of 329 clinic staff, interviews with clinic leaders, and analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 23 publications
2
61
0
Order By: Relevance
“…However, subgroup differences by age in testing and by race/ethnicity in HbA 1c testing and outcomes among disabled women suggest that subgroup-specific interventions may be needed to improve diabetes care. This is also consistent with a larger body of literature suggesting the lack of efficacy of global quality improvement programs for diabetes and hypertension (Grant et al, 2004;Murray et al, 2004;O'Connor et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…However, subgroup differences by age in testing and by race/ethnicity in HbA 1c testing and outcomes among disabled women suggest that subgroup-specific interventions may be needed to improve diabetes care. This is also consistent with a larger body of literature suggesting the lack of efficacy of global quality improvement programs for diabetes and hypertension (Grant et al, 2004;Murray et al, 2004;O'Connor et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…M a n y d i a b e t e s intervention studies are limited by inadequate sample size, nonrandomized patients and clinics, lack of control subjects, or limited scope of implementation within a single medical group or health system (11,13,14). Although some trials of quality improvement strategies have demonstrated small improvements in the process of care delivery, demonstrating improvement in control of A1C, LDL, and systolic blood pressure (SBP) has been more challenging (15)(16)(17)(18). The paucity of effective interventions improving diabetes care in primary care settings led us to design a "practical clinical trial" to test whether implementation of an organizational intervention could improve both diabetes care processes and clinical outcomes in primary care (19).…”
mentioning
confidence: 99%
“…The Chronic Care Model highlights the importance of a population-based approach; involving community, patients and providers; and information technology [4][5][6] . Various combinations of population management, practice support, and patient outreach have been used for diabetes care in a variety of settings with mixed results [7][8][9][10][11][12][13][14][15][16] . Many practice interventions for diabetes have been carried out in academic and urban centers.…”
mentioning
confidence: 99%